Five-year clinical outcomes of the first Korean-made sirolimus-eluting coronary stent with abluminal biodegradable polymer. Issue 19 (14th May 2021) - Seo, Kyoung-Woo; Yang, Hyoung-Mo; Yoon, Junghan; Kim, Hyo-Soo; Chang, Kiyuk; Lim, Hong-Seok; Choi, Byoung-Joo; Choi, So-Yeon; Yoon, Myeong-Ho; Lee, Seung-Hwan; Ahn, Sung Gyun; Youn, Young Jin; et al.
Abstract : Abstract: This study evaluated the 5-year clinical outcomes of the Genoss DES, the first Korean-made sirolimus-eluting coronary stent with abluminal biodegradable polymer. We previously conducted the first-in-patient prospective, multicenter, randomized trial with a 1:1 ratio of patients using the Genoss DES and Promus Element stents; the angiographic and clinical outcomes of the Genoss DES stent were comparable to those of the Promus Element stent. The primary endpoint was major adverse cardiac events (MACE), which was a composite of death, myocardial infarction (MI), and target lesion revascularization (TLR) at 5 years. We enrolled 38 patients in the Genoss DES group and 39 in the Promus Element group. Thirty-eight patients (100%) from the Genoss DES group and 38 (97.4%) from the Promus Element group were followed up at 5 years. The rates of MACE (5.3% vs 12.8%, P  = .431), death (5.3% vs 10.3%, P  = .675), TLR (2.6% vs 2.6%, P  = 1.000), and target vessel revascularization (TVR) (7.9% vs 2.6%, P  = .358) at 5 years did not differ significantly between the groups. No TLR or target vessel revascularization was reported from years 1 to 5 after the index procedure, and no MI or stent thrombosis occurred in either group during 5 years. The biodegradable polymer Genoss DES and durable polymer Promus Element stents showed comparable low rates of MACE at the 5-year clinical follow-up.